Analysis of Factors Influencing Cloth Diaper Purchase Decisions (A Study of Mothers in Medan City) - Lestari, Asri; Nurbaiti, Nurbaiti; Dharma, Budi (PT Mattawang Mediatama Solution, 2024)
This study aims to examine the influence of cultural factors, social factors, and personal factors on cloth diaper purchasing decisions. The study employs a quantitative methodology. The population of this study is mothers in the Medan city area. The study sample consists of mothers who have purchased and used cloth diapers on their children in Medan, with a total sample size of 100. The purposive sampling technique, is employed to get data from sample. Data collection is conducted using questionnaires. Statistical data analysis is performed using validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple regression analysis, coefficient of determination (R2), F tests, and T tests. The study findings indicate that cultural factors (X1) do not have a significant influence on purchasing decisions (Y). Social factors (X2) have a positive and significant influence on purchasing decisions (Y), and personal factors (X3) have a positive and significant influence on purchasing decisions (Y). Simultaneously, cultural factors (X1), social factors (X2), and personal factors (X3) have a significant combined influence on purchasing decisions (Y). Future research can be carried out involving a larger and more diverse sample, using more complex analysis techniques to obtain more generalizable results and can dig deeper into the factors and add specific factors that might influence the decision to purchase cloth diapers in the city of Medan or other regions in Indonesia.